PENGEMBANGAN E-MODUL BERBASIS FLIPBOOK MAKER PADA PEMBELAJARAN TEMATIK DISEKOLAH DASAR - Surahman, Surahman; Annurahman, Annurahman; Warnweri, Warnweri; Uraysalam, Uraysalam; Astuti, Indri (Jurnal Ilmiah Global Education, 2023)
This study aims to produce an e-module based on Flipbook Maker in the thematic learning of Grade 5 SD with the theme 6 of Heat and its Transfer to improve learning outcomes. To achieve the research objectives, the Research and Development (R&D) method was used with the Dick and Carey development model through 8 stages. This research and development produces E-modules like electronic books by designing and using flipbook makers in thematic learning in elementary schools on theme 6 Sub-theme 1 learning 1 to 6 grade 5 with the characteristics of this product that can be used on Android smartphones, laptops with the help of software and the internet network in which there are step menus leading to learning from the material menu the question menu, the observing menu, the information gathering menu, the reasoning menu, and the communicating menu. This research was conducted at SD Negeri 21 Riam Berasap with 72 research subjects consisting of fifth grade students with details of 3 students for one to one individual tests, 9 students for small group tests, and 30 students for field tests. As well as In this study involved 6 design expert validators, media experts, and thematic subject matter experts. Data from questionnaires and attitude scale instruments were analyzed by qualitative and quantitative analysis. Overall, from the results of data analysis (in the value range 1-5) the E-module is stated to be "very valid" with an average of 4.5. Thus, the analysis of empirical test data with individual test procedures, small groups, and field tests on 30 students of SDN Negeri 08 Siduk grade 5 shows the attitude of students is "very happy" using e-modules based on Flipbook maker using smartphone android, as well as leptopo with an average 80.9%. The e-module effectiveness test with the criteria of students' attitudes towards the e-module and pre-test and post-test scores involving 30 students turned out to be quite good which can be proven by the results in the data, the flipbook maker-based e-module in school thematic learning basic can be applied to grade 5 students.